Racial and ethnic inequities of palliative care use among advanced Non‐Small cell lung cancer patients in the US - Jessica Y. Islam; Dejana Braithwaite; Dongyu Zhang; Yi Guo; Tina D. Tailor; Tomi Akinyemiju (Cancer Medicine, 2023)
Abstract Background With early intervention, palliative care (PC) can improve quality of life and increase survival among advanced‐stage non‐small cell lung cancer (aNCSLC) patients. However, PC is often offered late in the cancer treatment course and is underused. We characterized racial/ethnic inequities and the role of healthcare access in PC use among patients with aNSCLC. Methods We used data from the 2004–2016 National Cancer Database, including adults aged 18–90 years with aNSCLC (stage 3 or 4 at diagnosis; n = 803,618). Based on the NCCN guidelines, PC includes non‐curative surgery, radiation, chemotherapy, pain management, or any combination of non‐curative care. We examined PC use by sociodemographic and health care‐level characteristics. To evaluate the independent associations of race/ethnicity and health care access characteristics with PC, we estimated adjusted odds ratios (aOR) with 95% confidence intervals (95% CI). Covariate adjustment sets varied by exposure determined using directed acyclic graphs. Results Our population was 55% male and 77% non‐Hispanic/Latinx (NH)‐White, with a mean age of 68 years. Overall, 19% of patients with aNSCLC used PC. Compared to NH‐White patients, NH‐Black (aOR:0.91,95% CI:0.89–0.93) and Hispanic/Latinx (aOR:0.80,95% CI:0.77–0.83) patients were less likely to use PC, whereas Indigenous (AI/AN) (aOR:1.18,95% CI:1.06–1.31) and Native Hawaiian/Pacific Islander (aOR:2.08,95% CI:1.83–2.36) patients were more likely. Overall, compared to the privately‐insured, uninsured (aOR:1.19,95% CI:1.11–1.28) and Medicaid‐insured patients (aOR:1.19,95% CI:1.14–1.25) were more likely to use PC. Conclusion PC is underutilized among NH‐Black and Hispanic/Latinx patients with aNSCLC. Insurance type may play a role in PC use among patients with aNSCLC.